The microbiome of Agaricus bisporus (Lange) Imbach and the prevalence of foodborne pathogens and mycoparasitic fungal pathogens in white button mushroom production systems - Korsten, Lise (University of Pretoria, 2024)
Thesis (PhD (Plant Pathology))--University of Pretoria, 2019.